Pengaruh Pembelajaran Aqidah Akhlak Terhadap Etika Berbusana Peserta Didik Diluar Sekolah - Nurhayati, Nurhayati (Indonesian Journal of Islamic Educational Review, 2024)
This thesis discusses the Influence of Aqidah Akhlak Learning on Dress Ethics Outside School Class XI Students at Madrasah Aliyah Negeri Palopo City. The research objectives are: 1) to find out the dress ethics of students outside of school. 2) to determine the effect of learning aqeedah morals on the dress ethics of students. The approach used in this research is quantitative with this type of survey research with a population of class XI at MAN Palopo City as many as 217 students. The sampling technique used in this study was random sampling and took 15% of the total population and obtained a sample of 32 students. Data collection techniques used: Observation, documentation, and questionnaires. Data analysis techniques used: validity test, reliability test, normality, linearity, and coefficient of determination test with the help of Microsoft Excel 2010 and SPSS for Windows Ver. 25. Based on the research that has been done, it can be concluded in this study that there is a positive and significant relationship between the influence of learning aqidah morals on dress ethics with the results of data analysis at the 5% interval level which shows that tcount aqidah morals = 3.535 is greater than ttable = 2.042. The results of the analysis on the R Square number in the calculation are obtained with a value of 0.057 or equal to 05.7%, which means that the great influence of learning aqeedah morals on dress ethics is 5.7% while the remaining 94.3% is influenced by other factors originating from beyond regression. In this research, it can be concluded that the dress ethics of class leave school well, neatly, politely and in accordance with the teachings of Islamic law.